2014
DOI: 10.1128/iai.01403-13
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pili in Enterococcal Pathogenesis

Abstract: cPassive protection, the administration of antibodies to prevent infection, has garnered significant interest in recent years as a potential prophylactic countermeasure to decrease the prevalence of hospital-acquired infections. Pili, polymerized protein structures covalently anchored to the peptidoglycan wall of many Gram-positive pathogens, are ideal targets for antibody intervention, given their importance in establishing infection and their accessibility to antibody interactions. In this work, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 52 publications
(71 reference statements)
0
44
0
2
Order By: Relevance
“…In addition, success in preventing endocarditis infection by a monoclonal antibody that targets the Ebp pili of E. faecalis has been demonstrated (42). Furthermore, it was recently shown that immunization with EbpA, the counterpart of EmpA in E. faecalis, provides protection against catheter-associated bladder infections in mice (38).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, success in preventing endocarditis infection by a monoclonal antibody that targets the Ebp pili of E. faecalis has been demonstrated (42). Furthermore, it was recently shown that immunization with EbpA, the counterpart of EmpA in E. faecalis, provides protection against catheter-associated bladder infections in mice (38).…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of bacterial CFU per gram were log transformed to negate the effect of large positive skewing of recovery values prior to performing unpaired t tests to obtain P values (21,56,(61)(62)(63)(64). Cultures yielding no growth were scored as sterile and were assigned a value of 1 CFU for statistical analysis or to obtain geometric means of CFU per gram of vegetation.…”
Section: Methodsmentioning
confidence: 99%
“…Cultures yielding no growth were scored as sterile and were assigned a value of 1 CFU for statistical analysis or to obtain geometric means of CFU per gram of vegetation. In animals that had only 1 colony recovered from the entire undiluted tissue homogenate, this value was converted to the number per gram of tissue (as was done with other recovered CFU) to determine the minimum detection limit (MDL) CFU per gram (21,56,(61)(62)(63)(64). Data and graphs were generated using Prism for Windows (version 4.00; GraphPad Software).…”
Section: Methodsmentioning
confidence: 99%
“…IgG Fab fragments against the aggregation substance AS were shown to confer partial protection against enterococcal endocarditis (45). In addition, passive immunization using a monoclonal antibody raised against the major component of E. faecalis pili, EbpC, significantly prevented the establishment of rat endocarditis (44). Our results with active vaccination using EfbA showed a significant reduction (Ͼ35%) in the number of immunized rats that developed E. faecalis infective endocarditis.…”
Section: Discussionmentioning
confidence: 57%
“…In this regard, there is increasing interest in the use of alternatives approaches to current antibiotic strategies such as the development of novel immunotherapies targeting proteins that are important for pathogenicity (41,42). MSCRAMMs, which are factors ubiquitously present in traditional and opportunistic Gram-positive pathogens, have been used as a target to develop vaccine candidates against E. faecalis (10,(43)(44)(45). Three proteins have been identified thus far as potential targets against E. faecalis endocarditis.…”
Section: Discussionmentioning
confidence: 99%